Community and public health nursing promoting the public's health - Rector, Cherie L. (Philadelphia Wolters Kluwer, 2018)
"The author weaves in meaningful, real-life examples, case studies, and perspectives to help students understand that transitions in care are critical in today's healthcare system. Covering a multitude of community and public settings, situations, and populations, the book helps students learn about promoting health, preventing disease (not just treating it), and protecting at-risk populations--including the elderly, the LGBT community, and veterans." -- Publisher.
Unit 1: Foundations of community health nursing -- Unit 2: Public health essentials for community health nursing -- Unit. 3: Community health nursing toolbox -- Unit. 4: The community as client -- Unit 5: The family as client -- Unit 6: Promoting and protecting the health of aggregates with developmental needs -- Unit 7: Promoting and protecting the health of vulnerable populations -- Unit 8: Settings for community health nursing.
Preceded by Community & public health nursing : promoting the public's health / [edited by] Judith Ann Allender, Cherie Rector, Kristine D. Warner. 8th ed. c2014.
Includes bibliographical references and index.
Keywords: Community health nursing -- United States; Public health nursing -- United States; Community Health Nursing; Public Health Nursing; Nurse's Role; Health Promotion; Community health nursing; Public health nursing; United States; United States